Prevalence of sports-related injuries in paralympic judo: An exploratory study - Fagher, K.; Ahmed, O. H.; Pernheim, N.; Varkey, E. (Journal of Science and Medicine in Sport, 2019)
Objectives: The aim was to assess the 1-year retrospective prevalence of athletes reporting a sports-related injury among Paralympic judokas with visual impairment (VI), and to identify any associations between injury, vision class, gender and weight category. Design: Cross-sectional retrospective study. Methods: The data were collected through an adapted questionnaire given to athletes with VI during an international training camp. A total of 45 Paralympic judokas answered the questionnaire. Descriptive statistics and chi-square statistics (p<0.05) were used to analyse the data. Spearman`s correlation was used to analyse multiple injuries. Results: Thirty-eight of the athletes reported an injury, giving a 1-year prevalence of 84% (95% CI 71-93). Male athletes reported significantly more injuries compared to female athletes (p=0.023). Over two thirds of the injuries (71%; 95% CI 55-83) had a traumatic onset. The majority of injuries (74%; 95% CI 58-85) occurred during judo training, and in the standing technique tachi waza (82%; 95% CI 66-91). The shoulder was the most single affected body location (29%). Forty-five percent of the injuries led to a time loss from sport for more than three weeks, and 40% of judokas reported multiple injuries. Conclusions: The results from this study demonstrate a high prevalence of mainly traumatic and severe sports-related injuries amongst athletes with VI participating in Paralympic judo. A first step towards prevention could be to minimize the time in tachi waza. However, to improve sports safety and to develop effective strategies for injury prevention, more comprehensive epidemiological studies, and also technical studies assessing injury mechanisms are warranted.